Defense Economic Strategy in Creating the Independence of the Indonesian Defense Industry (Case Study of the Independence of the Chinese Defense Industry) - Servasius Anu; Rizerius Eko Hadisancoko; Suwito Suwito (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Efforts to build an independent defense industry is a strategic goal in strengthening national identity. The aim of this research is to find out the Defense Economic Strategy in Realizing the Independence of the Indonesian Defense Industry. The results of the study show that one indicator of the independence of the defense industry is to produce its own defense and security equipment without any intervention from other countries. The Indonesian government must be able to make the independence of China's defense industry a spirit model for the development and independence of the Indonesian defense industry by consolidating and strengthening capital for the domestic defense industry, increasing competitiveness in producing defense products in global trade competition, and conducting collaborative technology transfer cooperation. to increase the ability of the national defense industry to realize the independence of the defense industry.